Heavy metal(loid)s migration mechanisms during soil erosion: A systematic quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Liang Tai; Nufang Fang; Yong Niu; Zeyan Wu; Zhiyong Fu; Kelin Wang (International Soil and Water Conservation Research)
Heavy metal(loid)s migration occurs in both particulate and dissolved forms during soil erosion, but it is unclear which form is dominant and which factors affect it. Thus, a quantitative synthesis of 379 global observations was conducted to assess heavy metal(loid)s migration mechanisms and a random forest analysis was used to assess the influence of key factors on the dissolved fraction of heavy metal(loid)s. Particulate-associated heavy metal(loid)s transport accounts for over 80% of the total. Heavy metal(loid)s migration forms are not significantly affected by experimental conditions (indoor simulated and field monitored), yet they vary between erosional and depositional zones. The dissolved percentage of Pb, As and Hg within areas of erosion were higher than in areas of deposition, while the opposite trend occurred for Cd, Cu, Zn, Cr and Ni. Soil Total Organic Carbon (TOC) was the most important factor affecting the migration of heavy metal(loid)s during soil erosion. Our results confirmed that heavy metal(loid)s usually migrate in association with fine-grained sediments due to their large surface area and high surface functional groups. These findings provide scientific guidance for further understanding migration mechanisms and the methods need to control heavy metal(loid)s transport during soil erosion.